Human Rights Provisions in Constitutions: Economic Opportunities and Challenges - Butt, Junaid; Kadry, Dalia (Acta Universitatis Danubius. Œconomica, 2025)
United Nations Human rights provisions in national constitutions have become increasingly significant in shaping economic opportunities and addressing challenges in contemporary societies (UNHR 1948). This study investigates the interplay between constitutional human rights and economic policies, focusing on how legal guarantees of economic and social rights, such as the right to work, property, and social welfare, impact economic growth, inequality, and poverty reduction. The research employs a comparative approach, analyzing constitutional frameworks across different countries to assess their effectiveness in promoting economic empowerment, stability, and inclusive growth. Using both qualitative and quantitative methods, the study evaluates the economic outcomes of these provisions and examines the challenges they present, including the tension between economic freedoms and social justice. The results suggest that while constitutional protections of human rights contribute to economic opportunities, they also create economic trade-offs, particularly in balancing market efficiency with social welfare needs. The study concludes that constitutional human rights provisions play a vital role in fostering inclusive economies but require careful calibration to ensure they effectively address economic disparities without hindering growth. This research highlights the importance of constitutional design in shaping national economic policies and offers valuable insights into how legal frameworks can be optimized to achieve both human rights and economic development goals.